ANALISIS PENGARUH JENJANG KARIR DAN KARAKTERISTIK PERAWAT TERHADAP PENERAPAN PRINSIP 6 BENAR PEMBERIAN OBAT SECARA INTRAVENA DI RUANG INAP RUMAH SAKIT SWASTA KOTA BANJARMASIN - Nursery, Septi Machelia Champaca; Chrismilasari, Lucia Andi (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2024)
Mistakes made when administering intravenous drugs to patients can jeopardize their safety. According to the PMKP report, there were three cases of medication administration errors in one private hospital in Banjarmasin City in 2018, four cases in 2019, two cases in 2020, and one in 2021. This study aimed to see how nurses' characteristics and career paths affect the application of the six correct principles of intravenous drug administration. This study was conducted using a cross-sectional research model. Thirty-five samples were taken through simple and cluster random sampling techniques. Observation sheets were used to collect data. For multivariate data analysis, frequency distribution and multiple linear regression were used. The results showed that nurses applied the six correct principles of intravenous drug administration in the excellent category as many as 23 respondents (65.7%), and the results of multiple linear regression tests obtained the results of a significant influence between career level variables on the application of the six correct principles of intravenous drug administration with a p-value of 0.033 (>0.05). This p-value indicates that the relationship between career level and applying the six correct principles of intravenous drug administration is statistically significant. At the same time, there was no significant influence between nurse characteristics, including age variables, gender, and education level, where the p-value successively on the age variable was 9.437, 0.605, 0.742, where the value was >0.05. The modeling results on each variable, namely career level and nurse characteristics, were simultaneously influenced by 0.481 (48%) in applying the six correct principles of intravenous drug administration. This means that career level and nurse characteristics explain 48% of the variation in applying these principles. Nurses have a graded career path from PK I to PK V, with higher levels of experience and knowledge that contribute to the application of nursing care. Nurses are also expected to have various characteristics that enable them to carry out and cooperate in the implementation of the six correct principles of intravenous drug administration, especially double-checking, asking for allergies to drugs, patient complaints before and after drug administration, checking drug expiration dates, patient identity, recording patient complaints, and patient reasons for refusing drugs. Keywords: career path, nurse characteristics, application of the six correct principles of intravenous drug administration